DECENTRALIZATION AND DIGITAL TRANSFORMATION AS THE BASIS FOR MODERNIZATION OF MANAGEMENT OF ECONOMIC DEVELOPMENT OF UKRAINE REGIONS - SHPILEVA, Vira; MELNYCHENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Under martial law, increasing economic challenges and the need to rebuild the country after large-scale destruction, the issue of effective management of the economic development of Ukraine's regions is of particular importance. In this context, decentralization and digital transformation are key factors in improving the functioning of the management system at the local level. They not only create conditions for increasing the capacity of territorial communities, but also ensure transparency, speed and adaptability of management decisions. The decentralization process that has been implemented in Ukraine since 2014 has significantly changed the approaches to the distribution of powers, financial resources and responsibilities between the levels of government. However, the effectiveness of this reform is largely determined by the ability of local authorities to implement modern management tools, in particular innovative digital tools. The integration of digital technologies into management activities allows for more effective monitoring of changes in socio-economic processes, involving citizens in decision-making and rapid response to challenges the integration of digital tools into the system of local economic development creates conditions for effective resource management and the development of investment attractiveness and the creation of new jobs, which is especially important in the context of post-war reconstruction.An important vector for the transformation of the governance system in Ukraine is the decentralization reform launched in 2014, which provides for the delegation of a wide range of powers and financial resources from the central government to the level of local communities. Decentralization helps to increase the efficiency of local self-government, develop infrastructure and stimulate economic growth of regions. It creates conditions for more autonomous decision-making, taking into account the specifics of each community, and at the same time improves the socio-economic indicators of the territories. The use of digital technologies also plays an important role in ensuring greater openness and accountability of the activities of authorities. Electronic platforms for public consultations, open data, electronic document management and public reporting systems make the activities of government bodies more open to citizens and businesses. This contributes to the formation of trust in the authorities and more active participation of society in decision-making processes, which is one of the important factors of democratic development.Decentralization and digital transformation are complementary processes that form the foundation for modernizing the management of economic development of Ukraine's regions. The transfer of powers and resources to the local level opens up new opportunities for improving the effectiveness of management decisions adapted to the specifics of the regions, their needs and potential. At the same time, digital technologies serve as a catalyst for these changes, ensuring the efficiency, transparency and accessibility of management processes, as well as the active participation of citizens in decision-making. Despite the numerous advantages, the processes of decentralization and digitalization face a number of challenges, including the uneven development of digital infrastructure, insufficient qualification of personnel, and legislative restrictions. To overcome these obstacles, an integrated approach is needed, which involves modernizing the regulatory framework, investing in digital technologies, increasing the competencies of local government employees and creating transparent mechanisms for interaction between the authorities and society.
Keywords: decentralization; digital transformation; regional development; economic governance; modernization; digital infrastructure; digital economy; regional policy